Pengenalan Aplikasi TikTok Sebagai Platform Digital Marketing Kepada iGeneration - Wardhanie, Ayouvi; Wibowo, Alexander; Arion, Benediktus; Putri Agustin, Heppy; Azmi Syahputra, Noval (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2024)
The community service aims to provide knowledge to the young generation, primarily middle and high school students, to get to know TikTok as an application that is not just entertainment but can also be used as a digital marketing medium for branding oneself and doing business. The method in this activity consists of three stages: preparation, which includes observing the application, reviewing problems, and creating modules; the second stage of implementation, which consists of workshops and consultations; and finally, the report, namely evaluation and journal publication. The results of this activity include training attended by six people from various schools in Indonesia and carried out online via Google Meet. Based on the results of the questionnaire via Google Form, overall, participants felt that the material provided was relatively straightforward to understand, participants were able to create content plans, and most importantly, they were able to hone their skills in business and personal branding on social media, especially on TikTok.